Carba‐Sugar Analogs of Glucosamine‐6‐Phosphate: New Activators for the glmS Riboswitch. Issue 3 (27th November 2022) - Stängle, David; Silkenath, Bjarne; Gehle, Paul; Esser, Anna; Mayer, Günter; Wittmann, Valentin
Abstract: Riboswitches are 5'‐untranslated mRNA regions mostly found in bacteria. They are promising drug targets to overcome emerging bacterial resistance against commonly used antibiotics. The glmS riboswitch is unique among the family of riboswitches as it is a ribozyme that undergoes self‐cleavage upon binding to glucosamine‐6‐phosphate (GlcN6P). Previously, we showed that carba glucosamine‐6‐phosphate (carba‐GlcN6P) induces self‐cleavage of the riboswitch with a potency similar to that of GlcN6P. Here, we report a synthetic approach to a new class of carba‐GlcN6P derivatives with an alkoxy substituent in the carba position. Key features of the synthesis are a ring closing metathesis followed by a hydroboration. The strategy gives access to libraries of carba‐GlcN6P derivatives. Ribozyme cleavage assays unraveled new activators for the glmS riboswitch from Listeria monocytogenes and Clostridium difficile . Abstract : A new class of carba‐sugars with an alkoxy substituent in the carba position has been synthesized. Key steps were a ring‐closing metathesis and a hydroboration. The compounds have been tested for their ability to induce self‐cleavage of the glmS ribozyme, which represents a potential drug target to fight bacterial resistance to antibiotics. Compound 32, with a methoxy substituent at the carba position, turned out to have the most promising properties.